PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROTATING TRIO EXCHANGE (RTE) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TATANAMA SENYAWA DAN PERSAMAAN REAKSI DI KELAS X IPA SMA NEGERI 1 SEBERIDA KABUPATEN INDRAGIRI HULU - Ningsih, Eplia Maya Ningsih Maya; Thaib, Armiyus Thaib (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to improve student achievement on the subject of nomenclature of compounds and chemical equations in science class X SMA Negeri 1 Seberida Indragiri Hulu. Form of research is experimental with pretest-posttest design. The sample consists of two classes, namely class X IPAB as experimental class and the class as a class XI IPAC controls randomly selected after tests of normality and homogeneity test. Experimental class were treated with the application of cooperative learning model rotating trio exchange (RTE) while the control class were not given the implementation of cooperative learning model rotating trio exchange (RTE). Data analysis technique used is the t-test. Based on the final results of data processing using t-test formula obtained t> t table ie 2.3836> 1.67 means that the implementation of cooperative learning model rotating trio exchange (RTE) can increase student achievement on the subject of nomenclature and the equation in the class X IPA SMA Negeri 1 Seberida Indragiri Hulu. The increased influence student achievement in experimental class is equal to 8.038%. Keywords: Cooperative learning, Rotating Trio Exchange (RTE), learning achievement